2010
DOI: 10.30935/cedtech/6039
|View full text |Cite
|
Sign up to set email alerts
|

Experiences from the Process of Designing Lessons with Interactive Whiteboard: ASSURE as a Road Map

Abstract: This study investigates university level students' experiences of designing lessons with an interactive whiteboard as an instructional medium. The sample consisted of 40 students who will be both moderator of technological resources in schools and computer teachers after graduation from university. In the design of a lesson process, the ASSURE instructional design model was their roadmap. The results showed that none of the students had used interactive whiteboards before the course. However, most of them knew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
23

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 13 publications
1
14
1
23
Order By: Relevance
“…Students have indicated that the interactive whiteboard enhances attention and interest towards the lesson. In other research studies that have been conducted, similar findings ere revealed − that interactive whiteboards increase the attention and motivation of students and thus they have a positive effect on their learning (Baran, 2010;Lai, 2010;Marzano, 2009;Slay, Sieborger & Hodgkinson-Williams, 2008). From this point of view, it can be said that the use of technology by the teachers in appropriate ways for the purpose of teaching or using the interactive whiteboard has positively affected the students.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Students have indicated that the interactive whiteboard enhances attention and interest towards the lesson. In other research studies that have been conducted, similar findings ere revealed − that interactive whiteboards increase the attention and motivation of students and thus they have a positive effect on their learning (Baran, 2010;Lai, 2010;Marzano, 2009;Slay, Sieborger & Hodgkinson-Williams, 2008). From this point of view, it can be said that the use of technology by the teachers in appropriate ways for the purpose of teaching or using the interactive whiteboard has positively affected the students.…”
Section: Discussionsupporting
confidence: 57%
“…For this reason, revealing attitudes and attitude-related conditions and taking measures based on research results are essential in reaching the target educational goal (Avcı, Coşkuntuncel & İnandı, 2011). Some research studies reveal that interactive whiteboards enhance attentiveness and motivation of students and, thus, influence their learning positively (Baran, 2010;Lai, 2010;Marzano, 2009;Slay, Sieborger & Hodgkinson-Williams, 2008). Torff & Tirotta (2010) reported that the use of interactive whiteboard technology was associated with upper elementary students' motivation in mathematics.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Sınıf odaklı modellerden biri olan Assure öğretim tasarım modeli, yeni öğretmenlere daha fazla uzman gibi düşünmelerine yardımcı olmak için izlemeleri için genel bir yol haritası sunmaktadır. Bu modeli okullardaki öğretmenler tarafından sıkça kullanılmasının temel nedeni, her birey için birkaç saatlik bir eğitim sağlamasıdır (Baran, 2010). Bu öğretim tasarımı modeli ile tasarlanan materyal ve öğrenme ortamları verilen cevaplara eksik öğrenmelerin olduğu tespit edildiğinde tekrar gözden geçirebilme imkânı sağlar (Çetinkaya, 2017).…”
Section: Introductionunclassified
“…Bununla birlikte, bu model temsil edilen ortamın karmaşıklığını, derin kimlik bilgilerini ve tasarımların yüksek revizyonunu gerektirmemektedir. Deneyimsiz bir öğretmen ve bir uzman öğretmen arasındaki temel fark, bir uzman öğretmenin içeriğe, uygun öğretim stratejilerine ve dağıtım ortamına kolayca karar verebilmesidir (Baran, 2010). Öğretimin önceden sistematik olarak planlanması ile birlikte materyal seçiminde ve kullanımında verimi arttırmayı hedefleyen Assure öğretim tasarımı modeli ile tasarlanan materyal ve öğrenme ortamları ile öğrencilerin, kazanım düzeyindeki sorulara verdikleri cevaplardan eksik öğrenmelerinin olduğu tespit edilen kazanımlar için modelleri tekrar gözden geçirebilme imkânı sağlar (Çetinkaya, 2016).…”
Section: Introductionunclassified
“…Dijital projeksiyon aletine ve bilgisayara bağlı olan, dokunmaya duyarlı, geniş bir tahta olan akıllı tahtanın öğretimdeki uygulamaları üzerine yapılan araştırmaların sayısı çok olmamakla birlikte her geçen gün artmaktadır (Becta, 2003). Son yapılan çalışmalar, interaktif özelliklerinden dolayı akıllı tahtaların konsantrasyonu ve dikkati artırdıkları ve böylece öğrencilerin başarılarını, motivasyonunu ve öğrenmelerini önemli oranda geliştirdiklerini göstermiştir (Baran, 2010;Emre, Kaya, Özdemir ve Kaya, 2011;Lai, 2010;Marzano, 2009;Slay, Siebörger ve Hodgkinson-Williams, 2008). Eğitim teknolojilerinin fen ve teknoloji derslerinde kullanılmasıyla birlikte öğrencilerin fen bilimlerine karşı olumlu tutum sergilemeye başladıkları da tespit edilmiştir (Pektaş, Çelik ve Katrancı, 2009).…”
Section: Introductionunclassified